2011
DOI: 10.1016/j.expneurol.2011.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Local modulation of striatal glutamate efflux by serotonin 1A receptor stimulation in dyskinetic, hemiparkinsonian rats

Abstract: Serotonin 1A receptor (5-HT 1A R) agonists reduce both L-DOPA-and D1 receptor (D1R) agonistmediated dyskinesia, but their anti-dyskinetic mechanism of action is not fully understood. Given that 5-HT 1A R stimulation reduces glutamatergic neurotransmission in the dopamine-depleted striatum, 5-HT 1A R agonists may diminish dyskinesia in part through modulation of pro-dyskinetic striatal glutamate levels. To test this, rats with unilateral medial forebrain bundle dopamine or sham lesions were primed with L-DOPA (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
80
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(90 citation statements)
references
References 71 publications
9
80
1
Order By: Relevance
“…17 However, whether D1R agonists directly induce glutamate release is less studied. In agreement with our previous work, 20 despite significant dyskinesia, treatment with the D1R agonist SKF81297 in hemiparkinsonian rats did not modify striatal glutamate levels ( Figure 5). However, striatal 5-HT 1A R stimulation alone diminished local glutamate (by ∼25%) and reduced it further (by ∼40%) when given with the D1R agonist.…”
Section: Acs Chemical Neurosciencesupporting
confidence: 93%
See 2 more Smart Citations
“…17 However, whether D1R agonists directly induce glutamate release is less studied. In agreement with our previous work, 20 despite significant dyskinesia, treatment with the D1R agonist SKF81297 in hemiparkinsonian rats did not modify striatal glutamate levels ( Figure 5). However, striatal 5-HT 1A R stimulation alone diminished local glutamate (by ∼25%) and reduced it further (by ∼40%) when given with the D1R agonist.…”
Section: Acs Chemical Neurosciencesupporting
confidence: 93%
“…1,16,65,66 However, the decrease in D1R agonist-induced AIMs by 5-HT 1B receptor agonism was moderate and rotational activity was not modified. 65 Importantly, in previous studies 7,20,37 and the current one (see Figures 4−6), the effects on AIMs and rotations were reversed with coadministration of the 5-HT 1A R antagonist WAY100635, further proposing the participation of this receptor subtype in our molecular and neurochemical effects. Nonetheless, future studies may wish to utilize lower concentrations of ±8-OH-DPAT in order to improve receptor specificity.…”
Section: Acs Chemical Neurosciencesupporting
confidence: 64%
See 1 more Smart Citation
“…In agreement with overactive glutamatergic transmission in LID and the antidyskinetic effect of various glutamate receptor antagonists, studies have demonstrated increased levels of glutamate in the striatum and increased levels of the GLT1 glutamate transporter in the basal ganglia of the dyskinetic 6-OHDAlesioned rat (Jonkers et al, 2002;Robelet et al, 2004;Dupre et al, 2011). Accordingly, decreasing glutamate release was proposed to be an effective way to alleviate dyskinesia.…”
Section: Glutamate Releasementioning
confidence: 78%
“…Stimulating the 5-HT autoreceptors has shown to reduce the activity of the raphe-striatal neurons, blunt the extracellular dopamine release in the striatum and attenuate the expression of LID in animal models of PD [7,8]. Stimulation of 5-HT1A and/or 5-HT1B receptors is also able to reduce D1-agonist-induced dyskinesia through a postsynaptic mechanism, (although, this require higher doses than those for attenuating LID) [14][15][16]. In line with this, recent data points to a role of 5-HT1A receptors expressed in primary motor cortex in the modulation of LID [17].…”
Section: Hope For New Anti-dyskinetic Drugs By 5-ht Receptor Modulationmentioning
confidence: 99%